Circulating biomarkers for prostate cancer. - Steuber, T; Helo, P; Lilja, H (2007)
Due to its significant applicability for early detection, risk prediction and follow-up evaluation, prostate specific antigen (PSA) has revolutionized our ability to treat prostate cancer patients. With the prevalent use of PSA for early detection during the last two decades, disease characteristics have been altered towards early detected, localized tumors with a high chance of cure following local therapy. This advantage faces the risk of overdetection and overtreatment. In addition, PSA lacks both, sensitivity and specificity to accurately detect patients at risk of prostate cancer. Therefore, novel biomarkers are urgently needed to improve identification of men at risk of having the disease and to predict the natural behaviour of the tumor. Recent advances in the evaluation of high-throughput technologies have led to the discovery of novel candidate markers for prostate cancer. This article will briefly discuss current PSA-based strategies and review several novel biomarkers for prostate cancer, detectable in blood.